Efficient Synthesis of 2-Methylenethiazolo[2,3-b]quinazolinone Derivatives - Mahdavi, Mohammad; Bialam, Maryam; Saeedi, Mina; Jafarpour, Farnaz; Foroumadi, Alireza; Shafiee, Abbas (Synlett, 2015)
Substituted o-amino-N-(prop-2-yn-1-yl) aromatic amides easily reacted with carbon disulfide (CS2) in the presence of potassium hydroxide (KOH) in EtOH under reflux conditions. Cyclization reaction followed by a favored 5-exo-dig ring closure afforded 2-methylene-thiazolo[2,3-b]quinazolinone derivatives in good yields.
Keywords: 2-methylene-thiazolo[2,3-b]quinazolinones; propargylamine; carbon disulfide; fused quinazolinone; 5-exo-dig